Effects of a mixture hylocereus polyrhizus (Red Dragon Fruit) juice and moringa leaf powder towards hemoglobin level in adolescent girls - Ester Angelina Winanti Ritonga; Tonny Cortis Maigoda (AcTion: Aceh Nutrition Journal, 2023)
Nutritional anemia in adolescents has an impact on decreasing learning concentration and low learning achievement. Adolescent girls who are anemic are at risk of becoming anemic women of childbearing age, then becoming anemic mothers who can experience chronic energy deficiency during pregnancy later. Red dragon fruit and moringa leaves are known to  have a high level of  vitamin C,  rich in iron, and other bioactive compound. However, the potency of the combination between Hylocereus polyrhizus juice and Moringa Leaf Powder towards Hemoglobin level in Adolescent girls is still remain unknown. The purpose of this study was to know the effect of giving a mixture  of hylocereus polyrhizus juice and Moringa leaf powder on hemoglobin levels in  adolescent girls. A Quasy Experimental study was conducted in this study with two intervention  groups and one control group. A purposive sampling technique was used to select 60 students especially adolescent girls from Senior High School 3 in Bengkulu City in May 2022. Statistical analysis using One Way Anova test and Bonferonni Post Hoc test. A mixture of Hylocereus polyrhizus juice and moringa leaf powder was significantly associated with increasing hemoglobin levels than group that was given hylocereus polyrhizus  juice only with p value = 0,000  (p <0,05).